2023
DOI: 10.1111/mpp.13340
|View full text |Cite
|
Sign up to set email alerts
|

Plant secondary metabolite citral interferes with Phytophthora capsici virulence by manipulating the expression of effector genes

Abstract: Phytophthora capsici is a notorious pathogen that infects various economically important plants and causes serious threats to agriculture worldwide. Plants deploy a variety of plant secondary metabolites to fend off pathogen attacks, but the molecular mechanisms are largely unknown. In this study, we screened 11 plant secondary metabolites to evaluate their biofumigation effects against P. capsici, and found that citral, carvacrol, and trans-2-decenal exhibited strong antimicrobial effects. Intriguingly, a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…32 In addition, citral has remarkable broad-spectrum inhibitory activities against bacteria and fungi. [21][22][23] Importantly, we found that citral exhibited good antifungal activity against R. solani with an EC 50 value of 28.86 mg L −1 (Table 1), indicating that citral could be used as a raw material to develop new antifungal agents against R. solani. Therefore, a new series of novel amide compounds bound to the citral skeleton and amide group were designed and synthesized to obtain new agents with good antifungal activity against R. solani; the general pathways are shown in Fig.…”
Section: Chemistrymentioning
confidence: 86%
See 1 more Smart Citation
“…32 In addition, citral has remarkable broad-spectrum inhibitory activities against bacteria and fungi. [21][22][23] Importantly, we found that citral exhibited good antifungal activity against R. solani with an EC 50 value of 28.86 mg L −1 (Table 1), indicating that citral could be used as a raw material to develop new antifungal agents against R. solani. Therefore, a new series of novel amide compounds bound to the citral skeleton and amide group were designed and synthesized to obtain new agents with good antifungal activity against R. solani; the general pathways are shown in Fig.…”
Section: Chemistrymentioning
confidence: 86%
“…[17][18][19] Owing to the presence of multiple unsaturated groups, citral has been investigated as a model compound for various reactions. 20 In addition, citral and its derivatives possess broad-spectrum antifungal activity against various plant pathogens, such as R. solani, Penicillium digitatum and Botrytis cinerea, [21][22][23][24] therefore citral can be used as an ideal lead structure for the development of antifungal agents owing to its original fungicidal effect.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been increasing interest in using microbial antagonists and natural plant products for the biological control of fruit postharvest diseases [38][39][40][41]. Some natural plant products, such as citral, jasmonates, benzaldehyde, and ethanol, have been found to have potential antimicrobial activity against postharvest pathogens [42], but research on these is still limited. In this study, a mustard cultivar called Dilong-1 was found to greatly suppress the mycelial growth of B. cinerea compared to other cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these assumptions open up certain attempts to understand. Lastly, citral inhibited the expression of certain effector genes and could decrease virulence of P. capsici towards its host [184]. This raises a whole new field of comprehension on a transcriptomic level about pathogen-host interactions modulated by EOC.…”
Section: Cellular Impacts Of Essential Oil Components On Oomycetesmentioning
confidence: 96%